Cysteine-Targeting Gd-Based Spin Label and Its Application in Electron Paramagnetic Resonance Spectroscopy - Yao, Xuemei; Landwehr, Eliane; Qi, Mian; Hülsmann, Miriam; Drescher, Malte; Godt, Adelheid (My University, 2025)
Highly selective and fast reactions at the thiol group of a cysteine-containing peptide or protein, giving a reduction-resistant linkage, are highly desirable for anchoring a paramagnetic label that enables structure determination with electron paramagnetic resonance and/or nuclear magnetic resonance spectroscopy. One possibility is the Michael addition of the thiol group onto a 4-vinylpyridine, which is a structural subunit of the labeling agent, e.g., of the complex 4-vinyl-PyMTA-Gd. This reaction, however, turned out to be too slow for broad applicability. If pyridine is exchanged for pyrimidine, this reaction becomes very fast while still being sufficiently chemoselective, as is demonstrated with reactions of the complexes 4-vinyl-PymiMTA-Ln with Ln = Gd and/or La, which contain a 4-vinylpyrimidine subunit, with cysteine, cysteine-containing oligoproline, and cysteine-containing thioredoxin. Furthermore, it was found that the complex PymiMTA-Gd is a suitable spin label for distance determination via double electron electron resonance spectroscopy. Interestingly, the EPR spectra of PyMTA-Gd and PymiMTA-Gd and their relaxation times are very similar. Obviously, the exchange of pyridine for pyrimidine has little effect on these relevant EPR spectroscopical properties. This indicates that other pyridine-containing Gd3+ complexes may be convertible in the same way to fast-reacting, ready-made spin labels while keeping their favorable EPR spectroscopical properties.
Keywords: 540